2008
DOI: 10.2323/jgam.54.267
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the probiotic potential of Lactobacillus paracasei KW3110 based on in vitro tests and oral administration tests in healthy adults

Abstract: Lactobacillus paracasei KW3110 is a strain which has been reported to possess a strong antiallergic activity. Since many lactic acid bacteria have shown to be useful as the probiotics, the possibility of this strain for use as a probiotic was studied. An in vitro test showed that this strain is strong enough to survive in the gastric juice. In addition, this strain showed exceptionally strong adherence to human intestinal epithelial cells, Caco-2 and HT29 compared to normal L. paracasei strains. Human oral adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Most probiotic strains are Lactobacilli which were isolated from infant, healthy adult, or fermented foods, generally evaluated by different selection criteria, which include: withstand transit through the gastrointestinal tract, the capacity to inhibit intestinal pathogens, the ability to colonize the intestinal tract, health benefits, etc. However, only probiotic strains surviving through the passage of the stomach and the small intestine have full scope to give the health benefits to the host [25,26]. Therefore, resisting gastric juice and bile salts in the gastrointestinal tract is the fundamental requirement [18].…”
Section: Discussionmentioning
confidence: 99%
“…Most probiotic strains are Lactobacilli which were isolated from infant, healthy adult, or fermented foods, generally evaluated by different selection criteria, which include: withstand transit through the gastrointestinal tract, the capacity to inhibit intestinal pathogens, the ability to colonize the intestinal tract, health benefits, etc. However, only probiotic strains surviving through the passage of the stomach and the small intestine have full scope to give the health benefits to the host [25,26]. Therefore, resisting gastric juice and bile salts in the gastrointestinal tract is the fundamental requirement [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although these LAB species might be indigenous in Dornogobi province, they appeared to be more frequent in tarag made with camel milk than that with other animal milks. Nishida et al (2008) reported that L. paracasei ssp. casei in the same cluster as both L. paracasei ssp.…”
Section: Nomentioning
confidence: 99%
“…For the manufacture of functional foods and beverages, LAB also have the advantage of the production of GABA using cheap ingredients, such as by-products in food industry (48). The GABA producing LAB act as probiotics but are only effective if they remain viable as they pass through stomach and intestine (14, 57). Three Lactobacillus strains, Lb.…”
Section: Introductionmentioning
confidence: 99%